RESEARCH OF MECHANICAL PERFORMANCE OF KNITTING CORD REINFORCED RUBBER HOSE - JIN YangFu; WU Hao; QIAN Xin (Jixie qiangdu)
Cord reinforced rubber hose was widely used in automobile,aviation,aerospace and other fields. Meeting mechanical performance was the key to the safe use. In this paper,modeling of knitting cord was probed firstly. Then mechanical performance of aramid cord reinforced EPDM rubber hose was analyzed by ANSYS. Finally influence of cord’s needle number on mechanical properties of rubber hose was researched. The results show that maximum stress of cord is more than three hundred of times of maximum equivalent stress of rubber and maximum deformation of rubber is several times of maximum deformation of the cord when hose is imposed 0. 24 MPa inner pressure. And rubber and cord will not be destroyed. Experimental Bursting pressure of rubber hose is 2. 04 MPa,which is 97% of forecast bursting pressure 2. 10 MPa. With cord ’s needle number increasing,equivalent stress and deformation of cord and rubber all decrease sharply at first then tend to be gentle.